An Evolutionary Insight Into the Heterogeneous Severity Pattern of the SARS-CoV-2 Infection - Raza, Rabail Zehra; Abbasi, Sumra Wajid (Frontiers in Genetics, 2022)
The ongoing pandemic of COVID-19 has elaborated an idiosyncratic pattern of SARS-CoV-2 induced symptoms in the human host. Some populations have succumbed to the SARS-CoV-2 infection in large numbers during this pandemic, whereas others have shown a resilient side by manifesting only milder or no symptoms at all. This observation has relayed the onus of the heterogeneous pattern of SARS-CoV-2 induced critical illness among different populations to the host genetic factors. Here, the evolutionary route was explored and three genetic loci, i.e. rs10735079, rs2109069, and rs2236757 associated with COVID-19 were analyzed. Among the three, the risk allele A at genetic locus rs2236757 residing in the IFNAR2 gene was observed to have undergone recent positive selection in the African population.